A Comparative Clinical Study of Mridweekadi Churna and Yavagrajadi Vati in Tundikeri (Tonsillitis) in Children (International Journal of Ayurveda and Pharma Research, 2024)
Tonsillitis is one of the common diseases in pediatric age group. In Ayurveda it can be correlated with Tundikeri, Which has been described under the Mukharoga. Description of Mridweekadi Churna is mentioned in Charaka Samhita in Trimarmiya Aadhyay under Mukha Rogas Chikitsa, and description of Yavagrajadi Vati is mentioned in Yoga Ratnakar in Mukha Roga Chikitsa Aadhyay. According to Acharya Vagbhata the main Dosha involved in Tundikeri is Kapha Dosha. Majority of ingredients of Mridweekadi Churna and Yavagrajadi Vati have Tikta, Kashaya, Laghu, Ruksha Guna, due to this it subsides Kapha Dosha. Therefore, a study was planned to compare the effect of both drug in Tundikeri (tonsillitis). Methods: Children, aged 5 to 16 years, suffering from tonsillitis were registered and categorized under two groups: group- A and group-B. Group A- Patients were treated with Mridweekadi Churna, and Group B- Patients were treated with Yavagrajadi Vati for 10 days and 7 days follow up also done by drug free period. Results: In Group-A, 55% patients were moderately improved and 45% patients showed mild improvements. In Group-B, 15% patients showed marked improvement, 75% patients were moderately improved and 10% patients showed mild improvement. Conclusion: Tonsillitis is an inflammation of the tonsils and it is a common childhood illness. During childhood period there is a natural dominancy of Kapha dosha and Tundikeri- a Kapha Pradhana disease (according to Acharya Vagbhata), hence children are more prone to it. To treat this, drugs should have the Kaphahar properties like Tikta, Kashaya ras and Laghu, Ruksha Guna. In this comparative clinical study both the chosen drugs, Mridweekadi Churna and Yavagrajadi Vati possesses all these properties and also are markedly effective in Tundikeri, but group B Yavagrajadi Vati display better results than Mridweekadi Churna. This study will also help future researchers to evaluate further in this research work.